How do you solve for y for the equation 2x–3y = 6?

We need to solve for y for the equation 2x–3y=6



Let us separate y term from rest of the terms bu transferring 3y to the right-hand side and brinf=ging 6 to left-hand side. We get

2x – 6 = 3y

Now dividing by 3 on both the sides of equation we get,

\(\frac{2x-6}{3}=\frac{3y}{3}\) \(\frac{2x}{3} – 2= y\)

Hence \(y = (\frac{2}{3})x-2\)


\(y = (\frac{2}{3})x-2\) for the given equation.

Leave a Comment

Your email address will not be published. Required fields are marked *


Free Class